1998
DOI: 10.1209/epl/i1998-00494-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the extreme UV opacity of a hot dense gold plasma

Abstract: The absorption of soft X-rays by gold at density of ≈ 0.01 g/cm 3 and temperature of ≈ 20 eV has been measured in the photon energy range of 50 to 300 eV. For that purpose, a thin gold foil tamped by carbon was heated by thermal X-rays generated in a laser-irradiated gold cavity and probed by X-rays emitted by a synchronized tungsten backlighter source. The measured absorption was compared with numerical calculations based on the super-transitionarray model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…For mid-and high-Z elements, however, there are systematic discrepancies unexplained so far [24][25][26]. Are these discrepancies caused by theoretical approximations or experimental uncertainties ?…”
Section: Radiative Opacity Of Au Plasmasmentioning
confidence: 99%
See 3 more Smart Citations
“…For mid-and high-Z elements, however, there are systematic discrepancies unexplained so far [24][25][26]. Are these discrepancies caused by theoretical approximations or experimental uncertainties ?…”
Section: Radiative Opacity Of Au Plasmasmentioning
confidence: 99%
“…So far, some researches have been carried out on the opacity of Au plasmas, both experimentally and theoretically. Eidmann et al [25] measured the opacity of a Au plasma at a density of ~ 0.01 g ⋅ cm −3 and temperature of~20 eV in a photon energy range of 50 to 300 eV. By mixing appropriate elements with Au, Orzechowski et al [67] experimentally demonstrated the increase of Rosseland mean opacity, which is 1.5 times higher than either of the constituents.…”
Section: Radiative Opacity Of Au Plasmasmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its importance in astrophysics, experimental data on the opacity of iron are extensive (Da Silva et al 1992;Springer et al 1992Springer et al , 1997Winhart et al 1995Winhart et al , 1996Chenais-Popovics et al 2000;Zhang et al 2012). Apart from iron, the opacities of low-Z (Perry et al 1991(Perry et al , 2000Yang et al 2002Yang et al , 2003Zhang et al 2007) and high-Z elements (Eidmann et al 1998;Zhang et al 2011) have also been measured in laboratories. However, the amount of laboratory measurements concerning the opacity of silicon is very limited.…”
Section: Introductionmentioning
confidence: 99%